Phase-coupled plasmon-induced transparency in integrated metal–dielectric–graphene–dielectric waveguide. (5th September 2017) - Yao, Xin-Tao; Lin, Qi; Zhai, Xiang; Su, Yi; Liang, Mei-Zhen; Liang, Mei-Zhu; Wang, Ling-Ling
Abstract: We theoretically and numerically investigate the phase-coupled plasmon-induced transparency effect in graphene plasmonic systems that consist of multiple cascade graphene nanoribbon resonators side-coupled to the bus waveguide. The formation of a transparency window is attributed to the superposition of the detuned resonances in graphene nanoribbons. The gap width between the metal and the graphene provides a new degree of freedom for controlling the round-trip phase accumulated in the bus waveguide, which determines the evolution of the transparency window in terms of intensity and symmetry. Our ultracompact configuration can realize slow light with group indices over 250 as well as retain high transmission intensity.